Socioeconomic mobility and talent utilization of workers from poorer backgrounds: The overlooked importance of within-organization dynamics - PITESA, Marko (Institutional Knowledge at Singapore Management University, 2019)
Socioeconomic mobility, or the ability of individuals to improve their socioeconomicstanding through merit-based contributions, is a fundamental ideal of modern societies.The key focus of societal efforts to ensure socioeconomic mobility has been on the provision of educational opportunities. We review evidence that even with the same education and job opportunities, being born into a poorer family undermines socioeconomicmobility because of processes occurring within organizations. The burden of poorerbackground might, ceteris paribus, be economically comparable to the gender gap. Weargue that in the societal and scientific effort to promote socioeconomic mobility, the keycontext in which mobility is supposed to happen—organizations—and the key part of thelife of people striving toward socioeconomic advancement—that as working adults—havebeen overlooked. We integrate the organizational literature, pointing to key withinorganizational processes impacting objective (socioeconomic) success with research,some emergent in organizational sciences and some disciplinary, on when, why, and howpeople from poorer backgrounds behave or are treated by others in the relevant situations.Integrating these literatures generates a novel and useful framework for identifying issuespeople born into poorer families face as employees, systematizes extant evidence andmakes it more accessible to organizational scientists, and allows us to lay the agenda forfuture organizational scholarship. Our hope is that the current review will help bringorganizational science—in our view, the best equipped domain of scholarship for studyinghow workers from different backgrounds fare in organizations—to the forefront of thequest for promoting socioeconomic mobility of workers coming from poorer families.